Law Enforcement of Narcotics Crimes Against Children in The Drug Investigation Directorate of The Bali Regional Police Force - Suyana, I Putu Dedy; H Nuriyanto RS; Zuhro Nurindahwati (PT FORMOSA CENDEKIA GLOBAL, 2024)
Children are a new generation of young people growing up in a nation, the child is a legal subject who has not reached the age of 18 (eighteen). Article 1 paragraph (15) of Law Number 35 of 2009 concerning Narcotics states that narcotics abuse is a person who uses narcotics without the right or against the law. If the perpetrator of the narcotics crime is a child, then in material law of course the child as the perpetrator of the narcotics crime can be charged following Article 112 of Law Number 35 of 2009, because the intended substance in the article is that it reads every person, which means that all people, both adults and children, can be subject to the article. narcotics abuse is qualified as a crime without a victim, which means that the victim of the crime is the perpetrator himself, so in the event of narcotics abuse, the victim (crime) is the child who abuses narcotics in addition to his qualifications as a perpetrator is a victim. So the investigators of the Bali Police Ditresnarkoba in enforcing the law on narcotics crimes against child perpetrators, attempted to do so through a diversion approach